2016
DOI: 10.15376/biores.11.4.8860-8874
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Corn Starch and Lignosulfonate Blend Film with a High Content of Lignosulfonate

Abstract: A degradable starch/lignin blend film was prepared using corn starch and sodium lignosulfonate via a casting and solvent evaporation method. The effect of sorbitol content on the swelling properties of starch/lignosulfonate blend films was investigated. The effect of lignosulfonate content on the swelling and mechanical properties was also studied. The results showed that when the mass ratio of sorbitol to starch changed over a wide range, from 0:9 to 9:9, the water absorption of the blend films increased at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The ultimate stress was reduced, and the hydrophobicity of films was improved with the lignosulfonates to starch ratio increasing from 1:9 to 9:9. The results from a scanning electron microscope (SEM), FTIR, and XRD revealed that there was good compatibility among lignosulfonates, starch, and sorbitol [91]. Vengal and Srikumar (2005) reported the results of water absorption and tensile tests of different starch-lignin polymer films.…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…The ultimate stress was reduced, and the hydrophobicity of films was improved with the lignosulfonates to starch ratio increasing from 1:9 to 9:9. The results from a scanning electron microscope (SEM), FTIR, and XRD revealed that there was good compatibility among lignosulfonates, starch, and sorbitol [91]. Vengal and Srikumar (2005) reported the results of water absorption and tensile tests of different starch-lignin polymer films.…”
Section: Application Of Lignin In Bioplasticsmentioning
confidence: 99%
“…Namely, they showed that chronic unpredictable mild stress significantly depletes the gut of Lactobacillus species ( Marin et al, 2017 ), a genus that has a capacity to produce high levels of H2O2, as a way to maintain their ecological niche. This peroxide has antimicrobial effects ( Eschenbach et al, 1989 ; Shi and Li, 2016 ), but it can also down-regulate host kynurenine metabolism by inhibiting IDO1. Indeed, stressed animals exhibited decreased levels of peroxide in their feces, correlating with the reduction of Lactobacilli levels, reduced expression of intestine IDO1, and decreased circulating levels of kynurenine.…”
Section: Kynurenine Metabolites Depression and Microbiotamentioning
confidence: 99%
“…175 Lignin (isolated and native) is an amorphous (non-crystalline) solid material, based not only on its theoretical structure (a highly complex branched configuration and its phenolic monomers structures make it amorphous) 176,177 but also on X-ray diffractometry (XRD) evidence. 178–181…”
Section: Thermal Analysis and Some Conceptual Errorsmentioning
confidence: 99%